BIOACTIVE COMPONENTS OF ETHYL ACETATE EXTRACT OF CASSIA FISTULA FLOWERS - Malik Fiaz Hussain Ferdosi; Arshad Javaid; Iqra Haider Khan (Journal of Animal and Plant Sciences, 2023)
This study was carried out to identify the phytoconstituents in ethyl acetate fraction of flower extract of Indian laburnum (Cassia fistula L.) and to enlist their bioactivities as reported in the literature. For this purpose, dry flowers of the selected plant species were extracted in methanol and the ethyl acetate soluble compounds of this extract were separated using separating funnel technique. The isolated ethyl acetate fraction was analyzed by GC-MS that indicated the presence of 39 phytoconstituents. Among these, 2-butenal, 2-ethyl- (21.12%), decane (9.13%) and 1-decanol, 2-hexyl- (8.09%) were identified as principal constituents. Four compounds namely cyclohexanone, 2,3-dimethyl- (4.45%), benzene, 1-ethyl-3-methyl- (3.18%), phenol, 4-propyl- (3.24%), and heptadecane (3.89%) were ranked as moderately abundant. Less abundant compounds included mesitylene (2.81%), nonane, 4-methyl- (2.79%), nonane, 3-methyl- (2.74%), nonadecane (2.66%), naphthalene (2.13%), tetratetracontane (2.05%), trifluoroacetoxy hexadecane (2.01%), octane, 2,5-dimethyl- (1.88%), nonane, 2-methyl- (1.75%), octane, 2,6-dimethyl- (1.66%), decane, 2,5,6-trimethyl- (1.71%), hexacosane (1.61%), heptadecane, 2,6,10,14-tetramethyl- (1.38%), benzene, 1,2,3-trimethyl- (1.38%), benzofuran, 2,3-dihydro- (1.34%), benzene, nitro- (1.24%), 17-pentatriacontene (1.31%), hexadecane (1.29%), pentadecane (1.46%), 5-octadecene, (E)- (1.13%), tetradecane (1.03%), and oxalic acid, allyl hexadecyl ester (1.01%). The remaining 9 compounds were present as the least abundant compounds with peak areas ˂1%. Literature showed that among the identified compounds, some possess antimicrobial, antioxidant, anti-inflammatory and anticancer properties.
Keywords: Flower extract; Cassia fistula; Ethyl acetate; GC-MS analysis; Phytochemical profile